The attitudes of the youth towards exorbitant `Enjugano' in Mbarara District, Uganda from 1970 to 1994 - Kiiza, Hilary (Kampala : Makerere University, 1995)
Thesis (M.A., Rel.Stud.) - Makerere University, 1995.
Includes bibliographical references (p. 222-229)
Keywords: Bride price -- Mbarara District; Youth -- Cross-cultural studies -- Attitudes -- Mbarara District